SEARCH FOR A NEUTRAL HIGGS PARTICLE IN THE DECAY SEQUENCE KL0-]PI-0H0 AND H0-]E+E- - Barr, G; Clarke, P; Coward, D; Cundy, D; Doble, N; Gatignon, L; Gibson, V; Grafstrom, P; Hagelberg, R; Kesseler, G; Vanderlans, J; Miczaika, T; et al. (1990)
We have searched for the sequence of decays KL0→π0H0 and H0→e+e- at the CERN Super Proton Synchrotron (SPS), and have allowed for a non-zero H0 lifetime. Three candidates have been seen, consistent with an expected background of 3.3. Limits on the branching ratio product in the range 10-8-10-7 are presented as a function of the mass and lifetime of the H0. These can be used to restrict the neutral Higgs of the minimal standard model.